Application of a scintillation gamma spectrometer for determination of radon content in water - Hakimov, D.А.; Zhuk, I.V.; Kievets, M.K. (Вопросы атомной науки и техники, 2021)
Experimental studies have been carried out to determine the sensitivity of a mobile scintillation gamma-spectrometer to radon-222 in mineral water samples for the selected measurement geometry and the minimum measurable activity of radon-222 in such samples. The measurement results of radon content in mineral water samples obtained using such gamma-spectrometer are presented too.